(untitled) (Biological Sciences - PJSIR, 2020)
Plasma membrane intrinsic proteins (PIP1) are the most common integral membrane proteins belong to a larger family of intrinsic aquaporin proteins. They are member of aquaporin gene family and have gained importance as highly expressed genes in plants. In this study, the promoter of aquaporin PIP1 gene was identified, analyzed and retrieved from high throughput genomic sequence (HTGS) database. The cis-acting regulatory elements, transcription start sites and transcription factor binding sites of selected promoter were identified through different bio-informatics tools. Many light responsive, phytohormone, stress and defense related cis-regulatory elements were detected in PIP1 promoter region indicating its role as a constitutive promoter. The PIP1 promoter was isolated from Solanum tuberosum. It was initially cloned in TA vector (pTZ57R/T) and later transferred to plant expression binary vectors, pGR1 and pGA482 for transient and stable expression studies in tobacco. The GUS expression results of PIP1 promoter in different tobacco tissues showed its functional importance in regulating gene expression in a constitutive manner. Further, it was concluded that the PIP1 aquaporin promoter is constitutively expressed with a strength equivalent to CaMV 2x35S promoter. These findings indicated the significance of isolated promoter for genetic engineering of plants for crop improvement.